Signifikasi Pendidikan Agama Islam Untuk Pembudayaan Keagamaan Bagi Anggota Polres Kabupaten Indramayu - Wawan Wahyudin (Risâlah Jurnal Pendidikan dan Studi Islam, 2024)
Internalizing good religious habits is everyone's hope in carrying out daily activities. Everyday life that is based on good intentions is the same as having the value of worship. As stated in this research, it seeks to find out about the importance of cultivating Islamic religious education for members of the Indramayu Police. This study aims to determine; 1) Analyzing the religious knowledge of the Indramayu Police Department members, 2) Analyzing the efforts to carry out religious empowerment for the Indramayu Police Department members, 3) Analyzing the results of religious acculturation for the Resort Police members. The method in this research uses a qualitative descriptive method. Data was obtained using observation, interviews and documentation methods. The results of the research obtained: Islamic religious education at the Indramayu Police Station is contained in the activities of reading the Al-Qur'an, Tahlilan and public recitations which are carried out on a scheduled basis. All of these activities were accepted as significant in cultivating religion at the Indramayu Police Station. The problems that arise in the implementation of the significance of Islamic religious education for religious acculturation for members of the Indramayu Regency Police are: 1) lack of motivation from the members, 2) difficulty dividing time with the duties carried out by the leadership to protect and protect the community, 3) lack of communication between the study manager and all members. The efforts to minimize this problem are: 1) providing good motivation by setting an example from the leaders. 2) manage time well and adjust to the schedule, 3) communicate with the leadership and the leadership coordinates with the recitation manager. The effectiveness and significance of Islamic Religious Education for religious cultivation for members of the Indramayu Police is very effective so that members' daily lives are worth worship starting with good intentions.